The supragenic organization of glycoside hydrolase encoding genes reveals distinct strategies for carbohydrate utilization in bacteria - Berlemont, Renaud (Frontiers in Microbiology, 2023)
Glycoside hydrolases (GHs) are carbohydrate active enzymes essential for many environmental (e.g., carbon-cycling) and biotechnological (e.g., biofuels) processes. The complete processing of carbohydrate by bacteria requires many enzymes acting synergistically. Here, I investigated the clustered or scattered distribution of 406,337 GH-genes and their association with transporter-genes identified in 15,640 completely sequenced bacterial genomes. Different bacterial lineages displayed conserved level of clustered or scattered GH-genes but overall, the GH-genes clustering was generally higher than in randomized genomes. In lineages with highly clustered GH-genes (e.g., Bacteroides, Paenibacillus), clustered genes shared the same orientation. These codirectional gene clusters potentially facilitate the genes co-expression by allowing transcriptional read-through and, at least in some cases, forming operons. In several taxa, the GH-genes clustered with distinct types of transporter genes. The type of transporter-genes and the distribution of the so-called GH:TR-genes clusters were conserved in selected lineages. Globally, the phylogenetically conserved clustering of GH-genes with transporter-genes highlights the central function of the carbohydrate processing across bacterial lineages. In addition, in bacteria with the most identified GH-genes, the genomic adaptations for carbohydrate processing also mirrored the broad environmental origin of the sequenced strains (e.g., soil, mammal gut) suggesting that a combination of evolutionary history and the environment select for specific supragenic organization of the GH-genes supporting the carbohydrate processing in bacterial genomes.